2004
DOI: 10.4269/ajtmh.2004.71.41
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Co-Infection With Human Immunodeficiency Virus Type 1 and Malaria in Pregnant Women in Sub-Saharan Africa

Abstract: In sub-Saharan Africa, human immunodeficiency virus (HIV) and malaria are among the leading causes of morbidity during pregnancy. We reviewed available information collected since the first report 15 years ago that HIV impaired the ability of pregnant women to control malaria parasitemia. Results from 11 studies showed that HIV-infected women experienced consistently more peripheral and placental malaria (summary relative risk = 1.58 and 1.66, respectively), higher parasite densities, and more febrile illnesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
246
5
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(270 citation statements)
references
References 141 publications
(226 reference statements)
15
246
5
4
Order By: Relevance
“…However, logistic regression analysis showed that anaemia was significantly and independently related to HIV infection. This finding corroborates previous reports [33,34].…”
Section: Discussionsupporting
confidence: 94%
“…However, logistic regression analysis showed that anaemia was significantly and independently related to HIV infection. This finding corroborates previous reports [33,34].…”
Section: Discussionsupporting
confidence: 94%
“…The detrimental effects of this interaction may be especially relevant during pregnancy, with adverse outcomes for both the mother and the infant [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a transient increase in peripheral HIV RNA viral load in adults and pregnant women with peripheral malaria which is resolved with effective antimalarial therapy [13][14][15][16]. As maternal HIV RNA viral load is a recognized risk factor for MTCT [6,7,11], it has been suggested that malaria, by increasing the replication of HIV, may increase the risk of MTCT [2,6]. However, studies assessing the impact of placental malaria (PM) on MTCT have produced conflicting results, suggesting either that PM could increase MTCT or that low-density PM parasitaemia could decrease MTCT [6,7,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In some high HIV prevalence locations, HIV-related TB is now the leading cause of maternal mortality. [6][7][8][9][10][11] The evidence highlights the inter-dependent nature of problems relating to HIV, HIV co-infections and pregnancy. It also points to the importance of integrated responses.…”
Section: Hiv and Maternal Healthmentioning
confidence: 99%